Characteristics of syphilis in the Dermato-Venereology Department of Bali Mandara General Hospital - Octaviani, Elrica Stella; Wahyuni, Luh Putu Dina (Bali Dermatology Venereology and Aesthetic Journal, 2024)
Introduction: Treponema pallidum is the sexually transmitted pathogen that causes syphilis. Congenital or acquired syphilis are the two categories. In 2020, the World Health Organization (WHO) anticipates 7 million additional cases of syphilis. 76,923 new patients were reported in 2020 by the Ministry of Health of the Republic of Indonesia. There is still inadequate information about Bali's incidence or prevalence of syphilis. This study aims to describe the characteristics of syphilis patients seeking treatment at Bali Mandara Hospital's Dermato-Venereology Department between 1st January 2020 to 31st December 2022. Methods: In this descriptive cross-sectional retrospective study from 1st January 2020 to 31st December 2022, we used 56 samples from secondary data collected from the patient register book and medical records of the dermatovenereology outpatient clinic at Bali Mandara General Hospital. Data were analyzed descriptively using SPSS version 26. Results: According to the study, there were 56 syphilis patients, including 32 men (57.1%) and 24 women (42.9%). The most common age group was 25 to 44 years old, with 36 patients (64.3%), while the most common clinical stage of syphilis was early latent syphilis, with 20 patients (35.7%). Venereal Disease Research Laboratory (VDRL) titer of 1:2 was the most frequent finding, with 16 patients (28.6%). Conclusion: It may be concluded that syphilis cases at Bali Mandara General Hospital have a different description that varies according to each variable. Future studies on syphilis cases are anticipated to build on the findings of this study.